1990
DOI: 10.1111/j.1600-0560.1990.tb00058.x
|View full text |Cite
|
Sign up to set email alerts
|

Altered expression of major histocompatibility complex (MHC) antigens by epidermal tumours

Abstract: Alteration in the major histocompatibility complex (MHC) antigen expression by cutaneous tumours may enable them to escape host defence mechanisms and to invade surrounding tissue. Immunohistochemical studies in a wide range of epidermally derived tumours demonstrated expression by keratinocytes of the class II molecule HLA-DR in squamous cell carcinoma (SCC) (2 of 8 cases) and keratoacanthoma (KA) (2 of 7 cases). Additionally, HLA-DP and DQ were expressed by single cases of SCC and KA, although, unlike the wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(8 citation statements)
references
References 26 publications
(12 reference statements)
0
7
0
1
Order By: Relevance
“…Supporting this supposition are numerous studies demonstrating an increase of activated intratumoral CD4-positive T cells (34,35), fewer numbers of eosinophils (36), and increased Langerhans' cells (37) in KA compared with SCC, and a high incidence of KAs in patients who experience immunosuppression (20,38,39). In addition, KAs can exhibit expression of human leukocyte antigen DR (40). Despite these findings in support of immunologically mediated regression, nonimmunologic mechanisms have been postulated (41) and by chromosomal analysis, KAs seem to be distinct from SCCs de novo (42).…”
Section: Discussionmentioning
confidence: 98%
“…Supporting this supposition are numerous studies demonstrating an increase of activated intratumoral CD4-positive T cells (34,35), fewer numbers of eosinophils (36), and increased Langerhans' cells (37) in KA compared with SCC, and a high incidence of KAs in patients who experience immunosuppression (20,38,39). In addition, KAs can exhibit expression of human leukocyte antigen DR (40). Despite these findings in support of immunologically mediated regression, nonimmunologic mechanisms have been postulated (41) and by chromosomal analysis, KAs seem to be distinct from SCCs de novo (42).…”
Section: Discussionmentioning
confidence: 98%
“…Associations between aberrant human leukocyte antigen (HLA) expression (75,76), or germline class-I and II allelic variations and keratinocyte carcinoma have been controversial (77)(78)(79)(80) and are affected by high UV exposure (81), immunosuppression (82), and HPV infection (83). Multiple variants in HLA-DRB1 ( Ã 01, Ã 07) have shown increased risk for BCC while HLA-DRB1 Ã 04 was protective (82).…”
Section: Germline Genetic Risk Factors and Risk Modelsmentioning
confidence: 99%
“…Multiple studies have shown that cSCC tumors also demonstrate high cell surface expression of class II HLA proteins [24–28]. Specifically, cSCC tumors most often express HLA-DR, though HLA-DP and DQ expression have also been reported [24,26]. Peripheral areas of cSCC tumors near inflammatory infiltrates show highest expression of class II HLA proteins [24–28].…”
Section: Resultsmentioning
confidence: 99%